FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Alfani Firaus; Vinola Herawaty; Andy Tjin (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
The objective of this research is to analyze: the influence of firm’s size on capital structure, the influence of profitability on capital structure, the influence of business risk on capital structure, the influence of time interest earned on capital structure, the influence of asset growth on capital structure, the influence of liquidity on capital structure, the influence of asset structure on capital structure, and the influence of managerial ownership on capital structure The research was conducted in the companies listed in Indonesian Stock Exchange except for banks and other financial companies during 2012-2015 observation period. This research is developed based on the previous research carried out by Firnanti (2011). The total samples taken by using purposive sampling method were 130 companies out of 351 companies. Multiple regression is used to analyze the hypothesis of this study.The result of this research found that (1) the size of the company's has a positive effect on the capital structure, (2) profitability has an adversely affect on the capital structure, (3) the business risk has no effect on capital structure, (4) time interest earned has no effect on the capital structure, (5 ) asset growth has a positive effect on the capital structure, (6) liquidity has a positive effect on the capital structure, (7) assets structure has a positive effect on the capital structure, and (8) managerial ownership affect positively on the capital structure.